Utilization of Lemongrass Essential Oil (Cymbogon winterianus Jowitt ex Bor) as a Hand Sanitizer - Alfi Sapitri; Vivi Asfianti; Eva Diansari Marbun (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
Hand sanitizer during the Covid-19 pandemic is very necessary to overcome community problems. Citronella (Cymbogon winterianus Jowitt ex Bor) is the species that produces the best essential oil compared to other species of citronella. The essential oil contained in citronella has properties, one of which is as an antiseptic. The purpose of this activity is for self-medication and optimizing the potential of citronella leaf herbal plants to become hand sanitizers as well as improving health and economy at the Medan Muslimah Foundation. This activity was carried out using the Focus Group Discussion (FGD) method. The solutions offered to overcome the existing problems are: 1. Observing partners regarding the condition of the partner group, 2. Formulating problems, 3. Providing solutions, 4. Conducting socialization and training, 5. Monitoring and Evaluation. The results of the evaluation of activities that were attended by 20 participants were based on the level of knowledge, 90% of participants had good knowledge and 10% had sufficient knowledge. As many as 80% of participants benefit from this activity and 100% feel usefulness, interest and satisfaction in the activity. The positive response given by the participants to the FGD and Training activities.